Correlations between molecular parameters of guest substances and their effect on model lipid membranes - Sadchenko, A.O.; Vashchenko, O.V.; Kasian, N.A.; Budianska, L.V.; Lisetski, L.N. (Functional Materials, 2016)
Effect of guests molecules on phase transitions of model lipid membranes was studied by differential scanning calorimetry. Membranotropic action of guest molecules was estimated from the shift of "gel - liquid crystal" phase transition temperature of lipid membranes. Relationships between membranotropic action and molecular parameters of guest molecules (volume, surface area, dipole moment, anisometry, lipophilicity coefficient, fraction of the polar area, etc.) were examined. For most of the lipophilic substances studied a high linear correlations between membranotropic action and lipophilicity coefficient (r = 0.86), as well as fraction of polar molecular area (r = -0.83) were established. For hydrophilic substances such correlations were not found. For groups of substances with similar chemical nature (glycerol derivatives, ammonium compounds), high linear correlations (r > 0.8) were established between membranotropic action and such molecular parameters as surface area, volume, dipole moment.